EVALUATION STUDY OF SOFT SOIL IMPROVEMENT WITH A COMBINATION OF PREFABRICATED VERTICAL DRAIN (PVD) AND MINIPILE(CASE STUDY ON BALIKPAPAN â SAMARINDA TOLL ROAD CONSTRUCTION PROJECT) - Wardoyo, Didik
Soil subsidence is a common problem in structures built on soft soil; this subsidence is caused by the process of groundwater dissipation over time. This is referred to as the consolidation process. Prefabricated vertical drains (PVD) can be used to accelerate the process of water dissipation in the soil. The embankment process in a high embankment structure must be in sync with the consolidation rate; there have been numerous cases of landslides caused by the speed and thickness of the embankment layer not being controlled. Because the consolidation process takes a long time in soft soils with high moisture content, it takes a long time to achieve a balance between the increase in bearing capacity of the soil and the embankment load. Increasing the initial bearing capacity of the soil can be done by reinforcing the minipile in order to achieve a balance between the embankment load and the bearing capacity of the soil in order to accelerate the embankment of the overlying soil. The amount of consolidation in the case of soft soil is calculated using the Finite Element method (Plaxis) and the direct observation method in the field based on monitoring data from geotechnical instruments.